Characteristics of personality profiles of elite wrestlers and basketball players - Kasum, G.; Bacanac, L.; Jakovljevic, S. (Acta Kinesiologica, 2011)
The aim of this study was to investigate personality of elite wrestlers and basketball players. Participants were 80 male elite basketball players and 47 elite wrestlers from Serbia. Participants had completed a Cattell's 16PF Questionnaire. Data analysis was done with basic descriptive statistics. Significance of differences between two groups was calculated with t - test in SPSS16 program. The results confirmed the hypothesis that the wrestlers and basketball players differ in the expression of certain forms of behaviour within certain dimensions of personality. Wrestlers had lower scores at factors: B - Reasoning, E - Dominance, F - Liveliness, G - Rule Consciousness, H -Social Boldness, N - Privateness and Q3 - Perfectionism. In other words they exhibit: lower developed ability of abstract thinking, higher level of reliability and sense of duty to the obligations, lower "super ego" strength, threat-sensitivity, and impulsivity. Basketball players had lower scores only at factor I - Sensitivity, it means that they are more independent, and realistic.